Overcoming the gap between child and adult mental health services: The Reggio Emilia experience in an early intervention in psychosis program. Issue 6 (2nd December 2020) - Poletti, Michele; Pelizza, Lorenzo; Azzali, Silvia; Paterlini, Federica; Garlassi, Sara; Scazza, Ilaria; Chiri, Luigi Rocco; Pupo, Simona; Raballo, Andrea
Abstract: Aim: Early intervention in psychosis (EIP) can reduce severity and persistence of illness. From September 2012, the Reggio Emilia Department of Mental Health developed the 'Reggio Emilia At‐Risk Mental States' (ReARMS) protocol as a specific EIP infrastructure in all its adult and child/adolescent mental health services. Aims of this study were (a) to describe the ReARMS macroscopic organization and (b) to analyse some specific process indicators (i.e., the amount of individuals referred to the ReARMS program, the number of subjects who met defined diagnostic criteria of early psychosis and accepted the intervention, and the 1‐year drop‐out rate) during the first 5 years of its clinical activity, in order to examine feasibility and quality of its procedures on the adolescent help‐seeking subgroup. Methods: Adolescent participants ( n  = 125), aged 13–18 years, completed the Comprehensive Assessment of At‐Risk Mental States (CAARMS) to investigate the clinical status. Descriptive quantitative analyses were then used. Results: Fifty (40%) individuals did not meet early psychosis‐defined criteria, while 75 (60%: i.e., 44 Ultra‐High Risk [UHR] and 31 First Episode Psychosis [FEP] subjects) were offered an EIP dedicated care protocol: of them, 66 (88%) were enrolled in the program and 9 (12%) dropped out during the first year of treatment). Adolescents enrolled in the ReARMS protocol were mainly referred by general practitioners (32%), family members (16%), or school/social services (15.2%). Seventy (56%) participants had a history of previous specialist contact (especially for learning and anxiety disorders). Conclusions: An EIP program for adolescents with early psychosis in Italian child/adolescent mental health services are feasible, clinically relevant and recommended, specifically in this age group with a high risk of falling through the child/adult service gap.